Mapping Space and Mobility in the Red Sea Region, c.1500–1950 - Miran, Jonathan (History compass, 2014)
Situated between the Indian Ocean and the Mediterranean and separating Northeast Africa from the Arabian Peninsula, the Red Sea is one of the most unique maritime spaces in the world and among the first to be mentioned in recorded history. This essay debunks past perceptions of this space as merely a maritime corridor and a transit space between the Mediterranean and the Indian Ocean. Instead, it promotes an effort to recast the history of the region with the Red Sea as an organizing framework for analysis, allowing us to imagine it as an integrated region sui generis characterized by multilayered, interconnected, and overlapping circuits and networks operating within and across it while still linked to both the Mediterranean and the Indian Ocean. The essay proposes a materially based analytical framework which can underpin several possible avenues for future research.